INVESTMENT ATTRACTIVENESS OF THE ORGANIZATION (Вестник университета)
The article is devoted to the review of existing problems and peculiarities in the evaluation of investment attractiveness. The article considers various approaches to the definition of the concept of «investment attractiveness» and the most relevant approaches to assessing the investment attractiveness of enterprises, and analyzes the factors of investment attractiveness that affect the activities of the organization. The content of the methodology for analyzing investment attractiveness is disclosed. It is proposed to identify the most significant groups of factors that influence the adoption of an investment decision and justify an integrated, multidimensional approach to the problem.